Pengaruh Likuiditas dan Ukuran Perusahaan Terhadap Tax Avoidance pada Sub Sektor Perdagangan Grosir dan Retail Di BEI - Della Heti Resvilia; Agnes Susana Merry Purwanti; Yohanes Suharsana (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2023)
The contribution of every taxpayer, both corporate and individual, to the state must submit an annual tax return. The higher the incoming income, the higher the amount of tax that must be paid by each taxpayer. It can lead to tax avoidance. Tax avoidance is an attempt to reduce the legal tax liability, causing many people and even businesses to engage in tax avoidance. The purpose of this study is to determine the effect of company liquidity and company size towards tax avoidance. Sample of this study were 54 companies in the wholesale and retail trading sub-sector of the Indonesian stock market for the period 2018 - 2020. Data analysis techniques used was multiple linear regression tests. The test results and research findings indicate that the liquidity variable has no effect on tax avoidance, which is caused by the company's ability to pay liabilitie. The company size variable has positive effect towards tax avoidance, because the company's balance sheet size as measured by Ln total assets affects the occurrence of tax avaidance.